Genetic Variation of the Endangered Neotropical Catfish Steindachneridion scriptum (Siluriformes: Pimelodidae) - Paixão, Rômulo V.; Ribolli, Josiane; Zaniboni-Filho, Evoy (Frontiers in Genetics, 2018)
Steindachneridion scriptum is an important species as a resource for fisheries and aquaculture; it is currently threatened and has a reduced occurrence in South America. The damming of rivers, overfishing and contamination of freshwater environments are the main impacts on the maintenance of this species. We accessed genetic diversity and structure of S. scriptum using the DNA barcode and control region (D-loop) of forty-three individuals from the Upper Uruguay river Basin (UUR) and ten sequences from the Upper Paraná river Basin (UPR), which were obtained from GenBank. S. scriptum from the UUR and the UPR were assigned in two distinct MOTUs (Molecular Operational Taxonomic Units) with higher interspecific K2P distance than the optimum threshold (OT = 0.0079). The COI Intra-MOTU distances of S. scriptum specimens from the UUR ranged from 0.0000 to 0.0100. The control region indicated a high number of haplotypes and low nucleotide diversity, compatible with a new population in recent expansion process. Genetic structure was observed, with high differentiation between UUR and UPR basins, identified by BAPS, haplotype network, AMOVA (FST = 0.78, p < 0.05) and Mantel test. S. scriptum from the UUR showed slight differentiation (FST = 0.068, p < 0.05), but not isolation-by-distance. Negative values of Tajima’s D and Fu’s Fs suggest recent demographic oscillations. A Bayesian skyline plot analysis indicated possible population expansion from beginning 2,500 years ago and a recent reduction in the population size. Low nucleotide diversity, spatial population structure and the reduction of effective population size should be considered for the planning of strategies aimed at the conservation and rehabilitation of this important fisheries resource.